Correlation between loge GDR and hyperuricemia in patients with type 2 diabetes mellitus: a cross-sectional study - Liu, Pei; Ji, Baolan; Peng, Yan (Frontiers in Endocrinology, 2025)
IntroductionHyperuricemia (HUA), an important health concern, is closely associated with insulin sensitivity. The natural log transformation of the glucose disposal rate (loge GDR) is a new model of insulin sensitivity in patients with type 2 diabetes mellitus (T2DM). The association between HUA and insulin resistance has been demonstrated by other insulin resistance indices. However, the correlation between loge GDR and HUA has not been explored. This study explored the interaction between loge GDR and HUA in patients with T2DM.MethodsThis study involved 2,352 patients with T2DM. Biochemical and clinical data were collected. Morning blood samples were collected after an overnight fast for serum uric acid measurement. All the parameters required for loge GDR calculation, including triglycerides, γ-glutamyl transferase, urinary albumin-to-creatinine ratio, and body mass index, were also collected. The correlation between the loge GDR and HUA was analyzed.ResultsPatients with HUA had lower loge GDR values than those without (P< 0.001). HUA prevalence decreased significantly with increasing loge GDR quartiles (P< 0.001). Multivariable regression analysis revealed that loge GDR was independently associated with HUA (odds ratio: 0.279, 95% confidence interval: 0.170–0.459). Loge GDR’s area under the receiver operating characteristic curve (0.706, 95%CI = 0.664-0.747) was superior to other indices.DiscussionLoge GDR correlates strongly with HUA and demonstrates significant HUA predictive value in patients with T2DM.